2019
DOI: 10.3390/nu12010087
|View full text |Cite
|
Sign up to set email alerts
|

The Timing Effects of Soy Protein Intake on Mice Gut Microbiota

Abstract: Soy protein intake is known to cause microbiota changes. While there are some reports about the effect of soy protein intake on gut microbiota and lipid metabolism, effective timing of soy protein intake has not been investigated. In this study, we examined the effect of soy protein intake timing on microbiota. Mice were fed twice a day, in the morning and evening, to compare the effect of soy protein intake in the morning with that in the evening. Mice were divided into three groups: mice fed only casein prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…Cecal SCFA concentrations were calculated as µmol/mg of dry cecal weight. This procedure of quantitative SCFA and lactic acid analysis was established in our papers [37,38,40].…”
Section: Measuring the Scfa And Lactic Acid Levels In The Cecummentioning
confidence: 99%
See 1 more Smart Citation
“…Cecal SCFA concentrations were calculated as µmol/mg of dry cecal weight. This procedure of quantitative SCFA and lactic acid analysis was established in our papers [37,38,40].…”
Section: Measuring the Scfa And Lactic Acid Levels In The Cecummentioning
confidence: 99%
“…Likewise, the study on effective nutrient intake timing in relation to the biological circadian rhythm is called chrononutrition. Previous studies have shown the importance of chronopharmacology and chrononutrition [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, they observed an increase in Bacteroidetes and Proteobacteria, as well as in Bifidobacterium and Enterococcus. On the other hand, they also addressed a decrease in Firmicutes and Lactococcus [ 66 ].…”
Section: The Influence Of Nutrition On the Microbiota And Agingmentioning
confidence: 99%
“…Inulin consumption at breakfast has a greater effect on the microbiota [15]. Tamura et al [16] investigated soy protein intake effects on intestinal microbiota. Soy protein intake whether in the morning or evening led to a greater microbiota diversity and a decrease in cecal pH resulting from SCFA production compared with casein intake [16].…”
mentioning
confidence: 99%
“…Tamura et al [16] investigated soy protein intake effects on intestinal microbiota. Soy protein intake whether in the morning or evening led to a greater microbiota diversity and a decrease in cecal pH resulting from SCFA production compared with casein intake [16]. Finally, Ahn et al [17] investigated the metabolomics changes in rats that received amlodipine.…”
mentioning
confidence: 99%